Bridging Organizational and Multilevel Networks in Adaptive Governance of the Preservation Area of Tanjung Binerean Wildlife Corridor, South Bolaang Mongondow Regency - Wijayanto, Kadek (KnE Social Sciences, 2025)
Tanjung Binerean is home to Sulawesi’s endemic maleo bird and other wildlife. Management and protection of this area is needed to ensure that the richness of animals in the wildlife preservation corridor is maintained. This research aims to see how bridging organizational and multilevel networks in the governance of Tanjung Binerean wildlife corridor preservation in South Bolaang Mongondow Regency can be implemented properly. It uses a qualitative approach and collects data through observation, in-depth interviews, and documentation. Data sources consist of primary and secondary data, while data analysis is carried out using interactive methods. The informants in this study were stakeholders and other parties directly involved in the implementation of preservation of the Tanjung Binerean wildlife corridor. The results of this study show that the government of South Bolaang Mongondow Regency has the main role in the management of the Tanjung Binerean Wildlife Corridor, especially since it is the driving force of collaboration forums with various parties both internal to the government and external parties at the local, national, and international levels. However, despite the active implementation of the forum with various elements of community, government, private sector, and organizations, the forum still cannot address problems such as the high rate of deforestation that threatens animal and plant habitats, especially in this corridor.